Investigating the Protective Effects of Vitamin D on Diabete - makan Cheraghpour; Farnoosh Naghashian; Elham Ehrampoush; Hosein Davoodi; Jalalaldin Mirzairazzaz; Reza Homayounfar (Fasa University of Medical Sciences, 2014)
Vitamin D directly (due to receptor activation by vitamin D) or indirectly (through regulation of calcium homeostasis) effects on the pathogenic mechanisms associated with both types of diabetes, such as pancreatic beta-cell dysfunction, impaired insulin action and systemic inflammation. It has been shown that using Vitamin D supplementation during pregnancy and infancy has relation with a reduced risk of type 1 diabetes. In non-obese diabetic mice studies, pharmacological doses of vitamin D can delay the onset of diabetes. Any direct link between vitamin D and risk of type 2 diabetes has not been established yet, however many questions such as the concentration of vitamin D for optimal glucose homeostasis and how long pursuit to understand the effect of vitamin D on insulin secretion and sensitivity is essential have not been fully answered. The use of 1, 25 (OH) 2D3 for preventing or treating diabetes through its hypercalcemic effects and bone turnover is limited. On the other hand however, the protective effects only observed in response to doses higher than the physiological levels. In any case, a better understanding of the role of vitamin D can lead to the development of preventive strategies for both types of diabetes..